Supraclavicular osteocutaneous free flap: Clinical application and surgical details for the reconstruction of composite defects of the nose - SAÇAK, BÜLENT (WILEY, 2015)
The supraclavicular fasciocutaneous flap is a well-recognized flap in head and neck reconstruction. In this report, we describe for the first time a variation of this flap, the osteocutaneous supraclavicular (SOC) free flap, which was used to reconstruct a composite nasal defect. The defect arose after resection of a recurrent squamous cell carcinoma and involved dorsal nasal skin, cartilage, and the entire nasal bone. A 6 cm x 4 cm size flap including skin, subcutaneous tissue, and a vascularized cortico-periosteal segment of the clavicle was raised based on the transverse cervical artery. The flap survived with no complications. A satisfactory aesthetic outcome was achieved following two revision procedures. We believe that the incorporation of bone to the supraclavicular flap may expand its applications in reconstruction of composite nasal and facial defects. (c) 2015 Wiley Periodicals, Inc. Microsurgery 35:328-332, 2015.
Keywords: TRANSVERSE CERVICAL ARTERY; PARAMEDIAN FOREHEAD FLAP; NASAL RECONSTRUCTION; NECK